Olympics during the pandemic: Predictors of Olympics viewing across platforms during the Tokyo Games - Tang, T.; Cooper, R. (Communication & Sport, 2022)
This research empirically tested the Dynamic Model of Exposure by examining users` multiplatform exposure during the Tokyo Olympic Games. Findings supported the model, suggesting that Olympics viewing was a dynamic process involving individual preferences and structures. Various preferences and structures combined to explain 37.7% of the variance in viewing the Olympics on television and 48.7% of Olympics viewing via digital streaming. Overall, endogenous preferences provided the largest predictive value, suggesting that pre-Olympic media routines had the most powerful influence on viewing this mega-event on both television and via digital streaming. Variables related to the COVID-19 pandemic showed no significant impact on those who watched the Tokyo Games.